CONSIDERATIONS ON USING THE SITUATIONAL CRISIS COMMUNICATION THEORY IN THE CRISIS COMMUNICATION PLANNING ACTIVITIES OF ROMANIAN ARMED FORCES’ INFORMATION AND PUBLIC RELATIONS STRUCTURES - George DAVID (Journal of Defense Resources Management, 2013)
Organizational crisis situations – quite frequently met in military establishments, as well – represent a major threat against reputation, one of the most important intangible resources that organizations own. The Situational Crisis Communication Theory (SCCT) suggests focusing managerial efforts in organizations facing crisis situations on preserving reputation through the proper management of stakeholders’ perceptions. Moreover, besides the theoretical framework, SCCT offers a wide range of practical tools to be used by managers and communication experts, tools which can be exploited successfully by the military information and public relations structures, too. This paper particularly focuses on the crisis communication planning effort, reviewing the main theoretical aspects of SCCT, as well as practical solutions which can be helpful to crisis communication planners.